A novel imaging method for quantitative Golgi localization reveals differential intra-Golgi trafficking of secretory cargoes - Tie, Hieng Chiong (2016)
Cellular functions of the Golgi are determined by the unique distribution of its resident proteins. Currently, electron microscopy is required for the localization of a Golgi protein at the sub-Golgi level. We developed a quantitative sub-Golgi localization method based on centers of fluorescence masses of nocodazole-induced Golgi ministacks under conventional optical microscopy. Our method is rapid, convenient, and quantitative, and it yields a practical localization resolution of ∼30 nm. The method was validated by the previous electron microscopy data. We quantitatively studied the intra-Golgi trafficking of synchronized secretory membrane cargoes and directly demonstrated the cisternal progression of cargoes from the cis- to the trans-Golgi. Our data suggest that the constitutive efflux of secretory cargoes could be restricted at the Golgi stack, and the entry of the trans-Golgi network in secretory pathway could be signal dependent.